(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Indian market today is commanded by the consumerism, especially following 10 years from economic reforms process. It is step by step being changed from a dominatingly venders market to a purchasers market where practiced decision by the consumers relies upon their awareness level. Consumer rights could be protected in an aggressive economy just when right guidelines for goods and services for which one makes installment are guaranteed by developing a network of institutions and legal protection framework. Guaranteeing consumer welfare is the obligation of the government as each subject of the country is a consumer in one way or the other. The present paper endeavors an expository, basic and engineered examination of consumer protection in India.